Efektivitas Media Video SADARI Terhadap Praktik SADARI pada Remaja Putri di SMK PGRI Sampit: The Effectiveness Media of SADARI Video on SADARI Practices of Young Women at SMK PGRI Sampit - Herlinadiyaningsih, Herlinadiyaningsih; Ayue, Heti Ira (Jurnal Surya Medika (JSM), 2022)
Breast Self-Examination (BSE) is a breast self-examination that is carried out to find an abnormal lump in the breast or detect breast cancer early, especially among young women who have not been exposed to information about BSE, especially among young women at SMK PGRI Sampit. This research aims to convey information and education among adolescents who have not been exposed to learning and knowledge about BSE, especially at SMK PGRI Sampit. The type of research used in this research is quasi-experimental research, with a "Nonequivalent Control Group Design" research design. The sampling technique used was the Nonprobability Sampling technique with the type of total sampling. The Wilcoxon Rank Test data analysis was used because it used a categorical measurement scale (Nominal/Ordinal) in pairs consisting of the pretest and posttest groups. The results of the Knowledge Analysis about BSE from the treatment group obtained p = 0.000, which means that there is an effect on the effectiveness of BSE learning through video media. In contrast, in the control group, the results are p = 0.253, which shows no influence from the knowledge of the control group on adolescent girls at SMK PGRI Sampit. Based on the results of the analysis of BSE practices in the Treatment group, a p-value = 0.000 was obtained, which indicated the effect of the effectiveness of BSE learning through video media, while in the control group, a p-value = 0.083, which showed no impact on BSE practice in the control group of adolescent girls at SMK PGRI Sampit. The results showed a significant p-value of 0.000 (< 0.05) which showed the effectiveness of BSE learning on video media for young women at SMK PGRI Sampit.